The demographics and geographic distribution of laboratory-confirmed Lyme disease cases in England and Wales (2013–2016): an ecological study. Issue 8 (18th August 2019) - Tulloch, John S P; Semper, Amanda E; Brooks, Tim J G; Russell, Katherine; Halsby, Kate D; Christley, Robert M; Radford, Alan D; Vivancos, Roberto; Warner, Jenny C
Abstract : Objective: Lyme disease is a tick-borne disease of increasing incidence and public concern across the Northern Hemisphere. However, the socio-demographics and geographic distribution of the population affected in England and Wales are poorly understood. Therefore, the proposed study was designed to describe the demographics and distribution of laboratory-confirmed cases of Lyme disease from a national testing laboratory. Design: An ecological study of routinely collected laboratory surveillance data. Setting: Public Health England's national Lyme disease testing laboratory. Participants: 3986 laboratory-confirmed cases of Lyme disease between 2013 and 2016. Results: In England and Wales, the incidence of laboratory-confirmed Lyme disease rose significantly over the study period from 1.62 cases per 100 000 in 2013 to 1.95 cases per 100 000 in 2016. There was a bimodal age distribution (with peaks at 6–10 and 61–65 years age bands) with a predominance of male patients. A significant clustering of areas with high Lyme disease incidence was located in southern England. An association was found between disease incidence and socioeconomic status, based on the patient's resident postcode, with more cases found in less deprived areas. Cases were disproportionately found in rural areas compared with the national population distribution. Conclusions: These results suggest that Lyme disease patients originate from areas with higher socioeconomic status and disproportionately in rural areas. Identification of the Lyme disease hotspots in southern England, alongside the socio-demographics described, will enable a targeted approach to public health interventions and messages.